2019
DOI: 10.24059/olj.v8i2.1826
|View full text |Cite
|
Sign up to set email alerts
|

University Instructors’ Reflections on Their First Online Teaching Experiences

Abstract: Moving from traditional face-to-face teaching to teaching online can be a precarious process for instructors. In this qualitative study, I interviewed instructors who were engaged in online teaching, for the first time, in a graduate program at a Canadian university. All instructors had some postsecondary face-to-face teaching experience. In-depth interviews with the instructors showed that they had very little knowledge of the new medium they were entering and relied heavily on their face-to-face experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 15 publications
4
51
0
6
Order By: Relevance
“…From on the categorization of discussion postings, it is also clear that the novice instructors were not providing much in the way of either information feedback or acknowledgement feedback as described by Graham et al [25]. This finding confirmed previous research that teaching online is a learning curve [18,19]; novice online instructors entered the new delivery medium with little knowledge of what online teaching means and the strategies that are effective in facilitating the online course.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…From on the categorization of discussion postings, it is also clear that the novice instructors were not providing much in the way of either information feedback or acknowledgement feedback as described by Graham et al [25]. This finding confirmed previous research that teaching online is a learning curve [18,19]; novice online instructors entered the new delivery medium with little knowledge of what online teaching means and the strategies that are effective in facilitating the online course.…”
Section: Discussionsupporting
confidence: 76%
“…In one of the major books on online teaching, Palloff and Pratt [18] recognized the difficulty in transitioning to the online environment and in working with courses developed by others. In a qualitative study, Conrad [19] interviewed novice online instructors in a graduate program and found that "their overall concerns were content-oriented" (p. 42). Although all considered themselves content deliverers, these first-time online instructors revealed little awareness of such issues as collaborative learning, learner's social presence, or the role of community building in the online learning environment.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The major implication includes the need for continuous training for HBCU faculty members to enhance their online teaching. Studies of online teaching have established that online instructors often rely on their past teaching experience when preparing to teach online (Choi & Park, 2006;Conceicao, 2006;Conrad, 2004). Faculty members whose experience has been confined to the traditional classroom cannot be expected to know how to design and deliver an effective online course (Palloff & Pratt, 2001).…”
Section: Practicementioning
confidence: 99%
“…There is a large body of literature that suggests online learning environments are well-suited to social constructivist learning environments, or communities of scientific inquiry, as called for by the national standards in professional development for science teachers. Research shows, however, that many novice online course developers have major misconceptions about the pedagogy that produces effective online learning [43]. This is not surprising since so little is known about online practices on a large scale, and in particular in science learning online.…”
Section: Research Questionsmentioning
confidence: 99%